(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The parents are the ones who have the biggest effect on the child’s progress from infancy to maturity. Consistency is one of the core characteristics of parenting behaviour. When children mature, families continue to have a significant role to play in their learning. In deciding the attendance and academic achievement of the infant, the parents’ positive attitude towards education of the children is significant.